SAT0168 Long Term Efficacy and Safety of Infliximab in the Treatment of BehÇEt'S Disease. (23rd January 2014) - Leccese, P.; Latanza, L.; Padula, A.; Nigro, A.; D'Angelo, S.; Gilio, M.; Palazzi, C.; Olivieri, I.
Abstract : Objectives: To evaluate the efficacy and safety of long-term administration of Infliximab in BD patients refractory to conventional therapy. Methods: In this ongoing, prospective, longitudinal and observational study BD patients unresponsive to conventional therapy with corticosteroids plus at least two different immunosuppressive drugs were treated with Infliximab therapy (5 mg/kg intravenously at weeks 0, 2, 6, and every 6-8 weeks subsequently). Response to anti-TNF therapy was based on the expert opinion and was graded as follows: remission, response, no response and worsening. Remission was defined as the complete disappearance of symptoms and signs of inflammation and response as at least 50% of improvement. Results: Since 2003, 68 BD patients (45 M/23 F; mean age 33.9±11.2 yrs; mean disease duration 12.4±9.5 yrs; 67% HLA-B51 positive) were enrolled. Indication for Infliximab treatment were uveitis in 35 patients, severe mucocutaneous manifestations in 14, CNS vasculitis in 11, optic neuritis in 1, intestinal involvement in 2, arthritis in 2, seizure in 2, vascular involvement in the remaining 1. The median duration of infliximab treatment was 25.5 months (range 1-106 months). Infliximab therapy resulted in a remission in 20 patients with uveitis, in 6 with CNS involvement, in 3 with severe mucocutaneous manifestations, in 1 with optic neuritis, in 1 with arthritis and in 1 with vascular involvement. A response was observed in 4 patients with mucocutaneous manifestations. The drug was stopped for lack of efficacy in 4 patients with severe mucocutaneous manifestations, 2 with uveitis, 2 with CNS vasculitis, 1 with seizure. Seventeen BD patients stopped infliximab therapy for loss of efficacy. Six BD patients discontinuated infliximab treatment for serious adverse events (5 for infusion reactions, 1 for bacterial pneumonia). Adverse events not requiring drug discontinuation were observed in 7 patients (mild infusion reactions in 2, upper respiratory tract infection in 6, urinary tract infection in 1). Conclusions: In our experience infliximab has been showed effective and safe in a long-term follow-up in patients with refractory BD. Disclosure of Interest: None Declared